The impact of psychological capital, psychological empowerment, and sports anxiety on the sports industry performance in Iraq Soccer Players - Haider H. Jawad; Qasim Khlaif Kadhim; Mufaq Saeed Ahmad; Moyaed Abdul allah Jasim; Tawfeeq Alghazali; Mohammed Kadhim Abbas Al-Maeeni (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The sports industry's performance in any nation relies on the performance of its players. The performance of soccer players in Iraq and the performance of the sports industry are declining. This study aims to examine the relationship between psychological capital, psychological empowerment, and sports anxiety in Iraqi soccer players. This study gathered quantitative data from Iraqi soccer players competing at the local, national, and international levels. This study employs partial least square – structural equation modeling to test its hypotheses. In addition, the purpose of this research is to enhance the performance of the sports industry in Iraq. This study revealed that psychological capital, psychological empowerment, and sports anxiety had a substantial impact on the success of the Iraqi sports business. This study introduced a new framework and substantially contributed to the corpus of knowledge. This study's theoretical and practical ramifications are equally noteworthy for enhancing the performance of the Iraqi sports business. This study's future directions would be useful for exploring future gaps in the literature.